Guide to network defense and countermeasures - Holden, Greg. ([S.l.] : Course Technology, 2003)
Network Defense and Countermeasures provides the reader with a solid foundation in network security fundamentals; while with the primary emphasis is on intrusion detection, the book also covers such essential practices as developing a security policy and then implementing that policy by performing Network Address Translation, packet filtering, and installing proxy servers, firewalls, and Virtual Private Networks. In addition, this text will prepare students to take the second exam, Network Defense and Countermeasures, for the Security Certified Network Professional (SCNP) Certification. This text assumes familiarity with the Internet and basic networking concepts such as TCP/IP, gateways, routers, and Ethernet.
Keywords: Computer networks -- Computer security -- Security measures